THE EFFECTIVENESS OF KNOW-WANTLEARNED (KWL) STRATEGY IN IMPROVING READING COMPREHENSION OF THE EIGHT GRADE STUDENTS OF SMP NEGERI 14 PALU - Syafi’i, Moh; Nurdin, Nurdin; Fitriningsih, Fitriningsih (Datokarama English Education Journal, 2020)
The problem focus of this research is to improve students reading comprehension by using Know-Want-Learned (KWL), to make the students comprehend the text, And how the students make their own conclusion about the text. The object of this research was the eighth grade students of SMP Negeri 14 Palu that were divided into two group that was controlled group and experimental group. The aim was to know their improvement after the treatment of KnowWant-Learned (KWL) technique. This research was quantitative research, and the procedure of collected the data were observation, interview, Pre test, treatment, and Post Test. The data analysis used statistical analysis that was descriptive analysis. Statistical analysis is used to test the hypothesis. And the formula used to test the hypothesis was t-test with the level of significance 0,05. The result showed that the application of Know-Want-Learned (KWL) strategy was successful in improving students’ reading comprehension. It can be proven with the result oftest of significance (t-test) was 0,2496. It means the result of t-test is more than level of significance (0,05). Based on the conclusion above, suggested to the teacher especially English teacher is to use Know-Want-Learned (KWL) strategy or find out the other method to make thestudents interest to the material.